2023
DOI: 10.1007/s00170-023-11118-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of tool parameter influence on the interlock forming during flat clinching process

Abstract: Tool parameters play a vital role in the mechanical interlock formation during the at clinching process, to understand the in uence of tool parameters on the interlock formation, the nite element software DEFORM-2D was used to build the numerical model of the at clinching process, and the numerical model was veri ed by the experiment. The in uences of the punch radius, punch llet radius, and blank holder radius on the interlock formation of the clinched joint were investigated using the numerical model. Then, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The numerical simulation indicated significant impact of the punch corner radius and the blank holder corner radius on the interlocking whereas the other parameters had little influence, Al5052 was used in the experimental configuration. and the same for (Wang et al, 2023) who elaborated on the influence of geometric parameters as punch radius, punch fillet radius and blank holder radius on flat clinching process, by choosing Al5052 as material for the study. A numerical simulation of flat clinching was investigated by (Chen et al, 2017) using Al1060 as material for sheets and validated by experimental results, the study showed the influence of punch and holder force diameters on the behavior of the joint, the neck thickness and interlocking length increase by the increase in punch diameter and decrease by the increase in blank holder force.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation indicated significant impact of the punch corner radius and the blank holder corner radius on the interlocking whereas the other parameters had little influence, Al5052 was used in the experimental configuration. and the same for (Wang et al, 2023) who elaborated on the influence of geometric parameters as punch radius, punch fillet radius and blank holder radius on flat clinching process, by choosing Al5052 as material for the study. A numerical simulation of flat clinching was investigated by (Chen et al, 2017) using Al1060 as material for sheets and validated by experimental results, the study showed the influence of punch and holder force diameters on the behavior of the joint, the neck thickness and interlocking length increase by the increase in punch diameter and decrease by the increase in blank holder force.…”
Section: Introductionmentioning
confidence: 99%